2012
DOI: 10.2178/jsl/1327068688
|View full text |Cite
|
Sign up to set email alerts
|

Forking and Dividing in NTP2 theories

Abstract: Abstract. We prove that in theories without the tree property of the second kind (which include dependent and simple theories) forking and dividing over models are the same, and in fact over any extension base. As an application we show that dependence is equivalent to bounded forking assuming NTP 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(124 citation statements)
references
References 8 publications
4
120
0
Order By: Relevance
“…Now g · X is also closed in G. So by results in [5] and [13] (see also [22]), g · X forks over M 0 . By the main result of [2] (which is maybe implicit in other papers in the o-minimal case), g · X divides over M 0 . As X is defined over M 0 this means that for some M 0 -indiscernible sequence (g i : i < ω) and some k < ω, {g i · X : i < ω} is k-inconsistent, in the sense that for every (some) i 1 < .. < i k , (g i 1 · X) ∩ .... ∩ (g i k · X) = ∅.…”
Section: Definition 41 Supposeκ Is An Inaccessible Cardinal Andm Amentioning
confidence: 83%
“…Now g · X is also closed in G. So by results in [5] and [13] (see also [22]), g · X forks over M 0 . By the main result of [2] (which is maybe implicit in other papers in the o-minimal case), g · X divides over M 0 . As X is defined over M 0 this means that for some M 0 -indiscernible sequence (g i : i < ω) and some k < ω, {g i · X : i < ω} is k-inconsistent, in the sense that for every (some) i 1 < .. < i k , (g i 1 · X) ∩ .... ∩ (g i k · X) = ∅.…”
Section: Definition 41 Supposeκ Is An Inaccessible Cardinal Andm Amentioning
confidence: 83%
“…Combined with the results on forking and dividing in NIP theories from [7], we deduce the following: working over a model M , let {φ(x, a) : a |= q(y)} be a family of non-forking instances of φ(x, y), where the parameter a ranges over the set of solutions of a partial type q. Combined with the results on forking and dividing in NIP theories from [7], we deduce the following: working over a model M , let {φ(x, a) : a |= q(y)} be a family of non-forking instances of φ(x, y), where the parameter a ranges over the set of solutions of a partial type q.…”
Section: Introductionmentioning
confidence: 91%
“…We will need some facts about forking and dividing in NTP 2 theories established in [CK12]. Recall that a set C is an extension base if every type in S(C) does not fork over C.…”
Section: Ntp 2 Implies the Chain Conditionmentioning
confidence: 99%
“…The realization that it is possible to develop a good theory of forking in the NTP 2 context came from the paper [CK12], where it was demonstrated that the basic theory can be carried out as long as one is working over an extension base (a set is called an extension base if every complete type over it has a global non-forking extension, e.g. any model or any set in a simple, o-minimal or C-minimal theory is an extension base).…”
Section: Introductionmentioning
confidence: 99%